The Gender Poverty Gap: What Can We Learn From Other Countries? - Lynne M. Casper; Sara S. MacLanahan; Irwin Garfinkel (Luxembourg Income Study (LIS), 1994)
Examines gender differences in poverty in eight industrialized countries: US, Canada, Australia, UK, Germany, Sweden, Italy and the Netherlands. Results suggest that gender differences in human capital factors and family factors, as well as religion, culture, and policy, all play a role in accounting for gender poverty gaps within and across countries.
Keywords: 330; Armut; Geschlecht; Industrieländer